Faktor-Faktor yang Berhubungan dengan Kejadian Kurang Energi Kronik (KEK) pada Ibu Hamil di Wilayah Kerja Puskesmas Kambangan - Sari, Marlynda Happy Nurmalita (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2024)
Chronic Energy Deficiency is a condition that must be watched out for because it can lead to maternal death if not handled properly. The purpose of this study was to determine the relationship between economic status and diet with KEK in pregnant women at the Kambangan Health Center. This study was an analytical survey with a cross-sectional approach. The population was 49 pregnant women in the third trimester or gestational age of more than 25 weeks, using purposive sampling. The results of the study showed that respondents aged 20-35 years were 43 respondents (88%). The last education of respondents was junior high school or equivalent, 21 pregnant women (43%). The husband's job was as a private employee, 20 respondents (41%). Pregnant women who were pregnant with their first child, 18 respondents (37%). Pregnant women who did not experience KEK were 27 respondents (55%). Pregnant women with husbands' incomes below the minimum wage were 29 respondents (59%). Pregnant women with poor diets were 29 respondents (59%). The results of the bivariate study showed that there was a relationship between diet and KEK in pregnant women with a p-value of 0.000. There is a relationship between economic status and KEK in pregnant women with a p-value of 0.000, the value is smaller than 0.05 (0.000<0.05). It is hoped that further research can provide more information about healthy eating patterns and provide knowledge for pregnant women who do not maintain their eating patterns.Â Â